ANALYSIS OF LEVEL OF SOCIAL DISCLOSURE IN SUSTAINABILITY REPORT AT PT BUKIT ASAM (PERSERO) TBK PERIOD 2017-2019 - onoadminmaster onoadminmaster (STIE Bangkinang Publishing, 2022)
This study aims to analyze level of social disclosure in Sustainability Report based on Economic, Environmental and Social categories at PT. Bukit Asam (Persero) Tbk. 2017-2019 period. The data of this research are secondary data from Sustainability Report analyzed using descriptive methods. The results showed that level of Social disclosure was higher than Economic and Environmental performance, the second highest level is Economic performance and Environmental performance places performance category with lowest percentage of disclosure. PT. Bukit Asam (Persero) Tbk. has made quality disclosures based on GRI-G4 Sustainability Reporting Guidelines with a value of 42.85% and can be classified as Partially Applied.